Pt-MoOx-carbon nanotube redox couple based electrocatalyst as a potential partner with polybenzimidazole membrane for high temperature polymer electrolyte membrane fuel cell applications - Vellacheri, Ranjith; Unni, SreeKuttan M.; Nahire, Sandip; Kharul, Ulhas K.; Kurungot, Sreekumar (Electrochimica Acta, 2010)
A redox couple based electrocatalyst comprising of Pt-Multi Wall Carbon NanoTube (Pt-MWCNT) promoted with molybdenum oxide (MoOx, 2 < x < 3) nanoparticles was prepared. The objective was to effectively organize the Pt-MoOx interface on the smooth MWCNT surface to overcome the practical difficulties associated with establishing such interface with Pt dispersed on carbon morphologies possessing surface irregularities. The present study revealed the importance of stringent controlling of the additive level for maintaining a balanced bifunctional behavior of the catalyst combination through the synergistic effects by the components and the need of a proton conducting membrane operable at high temperature to get better output from the Polymer Electrolyte Membrane Fuel Cell (PEMFC) systems. An indigenously developed polybenzimidazole (PBI) membrane was used to fabricate a membrane electrode assembly (MEA) as it can be operated at higher temperatures compared to that of Nafion membranes. MoOx additive level was carefully controlled by monitoring the active Pt area by cyclic voltammetry. All prepared electrocatalysts were characterized by using HRTEM, XRD and XPS to get information on dispersion and morphology, crystalinity and oxidation state of different elements, respectively. The system prepared with 5% MoOx addition with respect to Pt (hereafter Pt-MoOx(5%)-MWCNT) displayed balanced active Pt area and excellent oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR) activities. Rotating Disk Electrode (ROE) system was extensively utilized to understand the ORR kinetics and the favorable role of MoOx as the promoter in the reaction. The kinetic current (j(k)) measured at 0.02 V vs. Hg/Hg2SO4 electrode from the Koutecky-Levich plots was 9 times higher and the apparent activation energy during single cell evaluation was 27 kJ/mol lower for the MoOx promoted system, compared to the system without the additive. A higher operating temperature significantly favored the cell performance by a combined effect of enhancement in proton conductivity of the PBI membrane and possible kinetic benefit by the well postulated oxygen spill over effect by the MoOx type systems in some combinations involving such systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Methanol oxidation reaction; MWCNT; oxygen reduction reaction; PBI membrane; PEMFC

Hydrous RuO2-carbon nanofiber electrodes with high mass and electrode-specific capacitance for efficient energy storage - Vellacheri, Ranjith; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Nanoscale, 2012)
We demonstrate a new strategy for the fabrication of supercapacitor electrodes possessing high mass and area-specific capacitance for efficient charge storage, which can be extremely useful for the development of light, compact and high performance supercapacitors for a variety of high power demanding applications. High mass and electrode area specific capacitances were attained by using Hydrous Ruthenium Oxide (HRO)-Carbon Nanofiber (CNF) hybrid electrodes prepared by the deposition of HRO (similar to 31% Ru content) on both the outer and inner surfaces of a cylindrical hollow CNF having open tips. Electrochemical studies of the uniformly deposited HRO nanoparticles on the CNF surface showed a mass specific capacitance of 645 F g(-1) and an electrode specific capacitance of 1.29 F cm(-2) with a HRO-CNF material loading of 2 mg cm(-2) in the supercapacitor electrodes. The mass specific capacitance of pure HRO is 301 F g(-1), whereas the mass specific capacitance of HRO in the HRO-CNF electrode is similar to 1300 F g(-1), which is very close to the theoretical capacitance of HRO. This enhanced charge storage ability, high rate capability, better cyclic stability and low ESR of the HRO-CNF will be useful for the development of high performance supercapacitors.